A SYSTEM DYNAMICS MODEL FOR BIODIESEL INDUSTRY IN INDONESIA - Sulaim Arrumaisho, Ummu
Indonesia’s energy demand keeps increasing every year along with economic growth, population growth, energy prices, government policies, etc. On the other hand, oil reserves, natural gas reserves, and coal production keep decreasing. The biggest demand for energy in Indonesia is oil fuels that are consumed by six sectors, i.e. transportation, industrial, power plant, households, commercial and others. To fulfill this demand, Indonesia has to import oil fuels. In order to decrease oil import, Government of Indonesia develop some policies to use new and renewable energy such as biofuels. One of the biofuels that are currently used in Indonesia is biodiesel. Since 2009, biodiesel production in Indonesia has increased every year. The growth of biodiesel is influenced by several factors. To find out what factors and how these factors affect the growth of the biodiesel industry in Indonesia, this research was conducted using the literature study methodology and system dynamics modeling. Based on the literature study, the factors that influence biodiesel growth are feedstocks, biodiesel price, advanced technology, and the environment. In this research, the factors that are evaluated were feedstock, biodiesel price, and government mandatory and regulation. The evaluation was carried out through system dynamics modeling for the next thirty years. There were fifteen scenarios developed from five group scenarios, i.e. government mandates, government incentives, feedstock price, biodiesel price, and mix scenarios. The results of the system dynamics modeling simulation show that the factor that most influence the profit and biodiesel capacity construction is the use of advanced technology that can produce biodiesel from low quality and low-cost feedstocks. The second factor is government incentives in the form of a carbon tax that can increase the profit. The next factor is the amount of mandatory mixing of biodiesel in diesel oil. While biodiesel price factor did not significantly affect the profit and biodiesel capacity construction. In the next thirty years, the biodiesel industry in Indonesia has positive growth. The industry could apply the advance biodiesel production technology that can produce biodiesel from low quality and low-cost feedstock. Additionally, the government could implement carbon tax regulation to support biodiesel industry in Indonesia.